El Hombre de la Ventana - Torres, Martin (Revista Universidad de Guayaquil, 1998)
The man by the windowis losing the echo,he keeps peering out and findsnot even the grain of sugar from a kiss. The man by the window,looks, looks, searches and searchesfor lost letters, a verse,the cathedral of some prayer.